2017
DOI: 10.1080/13554794.2017.1290806
|View full text |Cite
|
Sign up to set email alerts
|

Added value and limitations of amyloid-PET imaging: review and analysis of selected cases of mild cognitive impairment and dementia

Abstract: Amyloid-positron emission tomography (PET) imaging of the brain detects elevated amyloid-beta (amyloid-β) neuritic plaques in vivo, which can be helpful in appropriately selected cases of mild cognitive impairment (MCI) and dementia, when Alzheimer's disease remains a possible etiology, after a comprehensive clinical evaluation. We reviewed cases of cognitively impaired patients who underwent amyloid-PET imaging because of diagnostic uncertainty. Pre- and post-PET elements of diagnosis and management were firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…First, in our work postmortem verification was not available and the main outcome measure was the change in diagnostic confidence, and this outcome reflects the beliefs of clinicians. However, the proportional change observed in diagnostic confidence is in agreement with others previous studies [18,27,35,37] with a similar methodological approach. Could be desirable that a long clinical follow-up of the population provides information on the relation of amyloid-PET results with the parameters of diagnosis certainty and treatment optimization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, in our work postmortem verification was not available and the main outcome measure was the change in diagnostic confidence, and this outcome reflects the beliefs of clinicians. However, the proportional change observed in diagnostic confidence is in agreement with others previous studies [18,27,35,37] with a similar methodological approach. Could be desirable that a long clinical follow-up of the population provides information on the relation of amyloid-PET results with the parameters of diagnosis certainty and treatment optimization.…”
Section: Discussionsupporting
confidence: 93%
“…In our opinion, although our subpopulations are different, they guarantee the whole spectrum of possibilities found in clinical practice (external validity). In general terms our results are in agreement with others works [17,35,37,38] using a different methodology to estimate diagnostic confidence as the percentage of increase in diagnostic confidence, reporting modifications from 16% to 26% (the modification in 1 step in the 5-point scale used in this work or in Ceccaldi et al, [18] implies a 20%), and in a population not restricted to AUC. [19]…”
Section: Discussionsupporting
confidence: 92%
“…However, in a “real-world” situation, heterogeneous groups of patients will be encountered as well. Six out of 13 studies were retrospective in nature [1820, 24, 25]. There was a possibility of publication bias according to our analyses, in that positive rather than negative findings tend to be reported in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…For studies that have reported a numerical measure in the change in diagnostic confidence, there was an overall increase in confidence in diagnosis that ranged from 16 to 44% (Table 1) [3, 17, 23, 27, 28]. For studies that reported on the change in confidence as categories, there were improvements in the category of confidence in 25–49.1% of patients (Table 1) [18, 30]. One study reported that the confidence in diagnosis of AD increased by 15.2% if the Aβ-PET was amyloid positive and decreased by 29.9% if amyloid negative (Table 1) [3].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to determine brain amyloid pathology has substantial clinical benefits and allows for improved confidence in the diagnosis of cognitive decline due to AD, as many studies have shown a positive correlation between Aβ PET‐positive individuals and their likelihood to progress to AD [2,3]. Additionally, amyloid status can alter the treatment and care decisions for individuals with mild cognitive impairment (MCI) and dementia [4,5]. The challenge with amyloid PET scanning is that it is not widely available [6] and is prohibitively expensive for many patients as it is not a covered service under Medicare [7,8].…”
Section: Introductionmentioning
confidence: 99%